2011
DOI: 10.1002/jcb.23008
|View full text |Cite
|
Sign up to set email alerts
|

The anandamide effect on NO/cGMP pathway in human platelets

Abstract: In this study the effect of the endocannabinoid anandamide on platelet nitric oxide (NO)/cGMP pathway was investigated. Data report that anandamide in a dose-and time-dependent manner increased NO and cGMP levels and stimulated endothelial nitric oxide synthase (eNOS) activity. These parameters were significantly reduced by LY294002, selective inhibitor of PI3K and by MK2206, specific inhibitor of AKT. Moreover anandamide stimulated both eNOSser1177 and AKTser473 phosphorylation. Finally the anandamide effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…We have shown that AEA stimulated eNOS phosphorylation in a dose‐dependent manner peaking at 10 μM (Fig. a) as previously published (Signorello et al, ). Several authors (Liu et al, ; Thors et al, ) reported that AMPKα can phosphorylate eNOS on ser1177, its positive regulatory site.…”
Section: Resultssupporting
confidence: 89%
“…We have shown that AEA stimulated eNOS phosphorylation in a dose‐dependent manner peaking at 10 μM (Fig. a) as previously published (Signorello et al, ). Several authors (Liu et al, ; Thors et al, ) reported that AMPKα can phosphorylate eNOS on ser1177, its positive regulatory site.…”
Section: Resultssupporting
confidence: 89%
“…To some extent these results were similar to the reports previously described [3,26], although the PLTs were incubated at 37°C in their studies. Previous studies also showed that millimole concentrations of ANA were able to activate human PLTs [6,16], but these levels are much higher than those in the blood [27].…”
Section: Discussionsupporting
confidence: 83%
“…So it has been speculated that the anti-apoptotic action of ANA can also occur in vivo [3]. Recently, Signorello et al reported that low concentrations of ANA contributed to extending PLT survival, through PI3K/Akt pathway activation, stimulating endothelial nitric oxide synthase activity and increasing nitric oxide (NO) levels in human PLTs [26]. Increasing the NO level in human PLTs could be one of many beneficial effects produced by ANA during ischemic conditions [29], as ANA produces vasodilatation in the arterial system [30].…”
Section: Discussionmentioning
confidence: 98%
“…dl-Nebivolol and l-nebivolol enhanced eNOS phosphorylation at serine1177, 1 of the phosphorylation sites involved in eNOS activation in platelets. [42][43][44] Tran Quang et al 45 showed that both d-and l-nebivolol stimulate vascular β3-adrenoceptors in rat aortae, and that this may be relevant to nebivolol-induced NO release. However, the presence of β3-AR has not been demonstrated in platelets that instead possess β1-and β2-AR.…”
Section: Discussionmentioning
confidence: 99%